(untitled) (Journal of Engineering, 2024)
. The primary goal of this investigation is to study the effect of using mono and hybrid fibers on the fresh and hardened characteristics of Lightweight Self-Compacting Concrete (LWSCC). Slump flow test, L-box test, sieve segregation test, and V-funnel test were used to evaluate the workability of LWSCC. The mechanical characteristics of LWSCC were assessed by using compressive strength, splitting strength, and flexural strength. Four mixtures using two types of fiber: Steel fiber (St) and polypropylene fiber (PP) (0% fiber, 1% (St), 0.75% (St) +0.25% (PP), 0.5% (St) +0.5% (PP)) were made. According to the results, (St) fiber and hybrid fiber addition to LWSCC reduced its workability, although the values of tests were still within the acceptable range stander of EFNARC. The findings indicated a decrease in the values of slump flow and L-box test by adding mono and hybrid fibers to the LWSCC mixture. While the T500mm and V_ funnel tests increased by adding mono and hybrid fibers to LWSCC mixture. The results also indicate that the utilisation of (St) fiber and hybrid fibers had a significant effect on the mechanical characteristics of LWSCC. Where the flexural and splitting strengths significantly increase with the addition of (St) and hybrid fibers to the LWSCC mix.